MENTAL HEALTH OF INFORMAL CAREGIVERS : MENTAL HEALTH OF INFORMAL CAREGIVERS - Rajovic, Tatjana; Milic, Natasa (Medicinski podmladak, 2022)
Aging society is facing an important public health problem related to provision of care to older and dependent people. The care provided on a daily basis includes a range of different health and social services, as well as the provision of emotional support to people who are unable to function independently. Activities important for daily functioning, such as bathing, dressing, feeding, shopping and health monitoring are only part of the responsibilities and obligations that the "invisible workforce", i.e. informal carers, must provide. Even though, regardless of the heavy price informal caregivers often pay with their economic and health status, they still remain a blind spot in public policies. An informal caregiver is a person who provides ongoing care and assistance without payment to family members and friends who need support due to physical, cognitive or mental problems. Depression is one of the most common problems faced by informal carers and it is estimated that a large number, between 40% and 70% of all informal carers have symptoms of depression. The COVID-19 pandemic has had an impact on physical health, however as the pandemic continues, it has an increasing impact on the mental health of people all around the world, where informal carers fall into a particularly vulnerable category. Informal carers, especially those who provide long-term care to a family member, were at increased risk of physical and emotional exhaustion due to the burden of care, reduced services, as well as its relocation to the telephone consultation and digital sphere, which increased stress and risk of having mental health problems. While some informal caregivers managed to cope with stress and developed resilience, others did not and psychological pressure led to the development of depressive symptoms and depression itself.  Key words: informal caregiver, mental health, COVID-19
Keywords: informal caregiver; mental health; COVID-19